2022
DOI: 10.3390/jcm11133883
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Dysfunction during Acute SARS-CoV-2 Infection: A Systematic Review

Abstract: Although autonomic dysfunction (AD) after the recovery from Coronavirus disease 2019 (COVID-19) has been thoroughly described, few data are available regarding the involvement of the autonomic nervous system (ANS) during the acute phase of SARS-CoV-2 infection. The primary aim of this review was to summarize current knowledge regarding the AD occurring during acute COVID-19. Secondarily, we aimed to clarify the prognostic value of ANS involvement and the role of autonomic parameters in predicting SARS-CoV-2 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 113 publications
1
26
0
Order By: Relevance
“…Future studies should investigate the criteria for scanning cardiac changes, as well as new approaches such as cardiac autonomic assessment. Some studies suggest that cardiac autonomic impairment is also involved during COVID-19 infection and is related to worse prognosis [ 23 ]. The study of cardiac autonomic modulation can be easily performed through non-invasive assessment based on heart rate variability, which is a predictor index of morbidity and mortality in patients with cardiovascular disease.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should investigate the criteria for scanning cardiac changes, as well as new approaches such as cardiac autonomic assessment. Some studies suggest that cardiac autonomic impairment is also involved during COVID-19 infection and is related to worse prognosis [ 23 ]. The study of cardiac autonomic modulation can be easily performed through non-invasive assessment based on heart rate variability, which is a predictor index of morbidity and mortality in patients with cardiovascular disease.…”
Section: Perspectivesmentioning
confidence: 99%
“…The study of cardiac autonomic modulation can be easily performed through non-invasive assessment based on heart rate variability, which is a predictor index of morbidity and mortality in patients with cardiovascular disease. A recent study suggested that the cardiac autonomic nervous system imbalance, assessed by heart rate variability, may be a prominent feature of acute COVID-19 [ 23 ]. However, to the best of my knowledge, there are no studies on this relationship in athletes infected with COVID-19.…”
Section: Perspectivesmentioning
confidence: 99%
“…Cheshire et al have argued that the etiological agent of sweating disease would likely be a virus affecting the autonomic nervous system [ 172 ]. Interestingly, autonomic dysfunction, sometimes with hyperhidrosis, is a prominent feature of acute SARS-CoV-2 infection [ 178 , 179 ]. Rhabdoviruses, a virus family to which for instance rabies virus belongs, may likewise be a possibility to be considered.…”
Section: Resultsmentioning
confidence: 99%
“…Cheshire et al have argued that the etiological agent of sweating disease would likely be a virus affecting the autonomic nervous system [166]. Interestingly, autonomic dysfunction, sometimes with hyperhidrosis, is a prominent feature of acute SARS-CoV-2 infection [172,173]. Rhabdoviruses, a virus family to which for instance rabies virus belongs, may likewise be a possibility to be considered.…”
Section: Historical Publications As a Source Of Past Epidemicsmentioning
confidence: 99%